SPATIO-TEMPORAL THERMAL FRONTS DISTRIBUTION DURING JANUARY-DECEMBER 2018 IN THE MAKASSAR STRAIT: AN IMPORTANT IMPLICATION FOR PELAGIC FISHERIES - Zainuddin, Mukti; Mallawa, Achmar; Safruddin, Safruddin; Farhum, St. Aisjah; Hidayat, Rachmat; Sahni Putri, Andi Rani; Ridwan, Muhammad (Hasanuddin University, 2020)
Makassar Strait has been identified as an area of interesting studies for marine science and operational fisheries. It provides the unique ocean structures such as topographic feature, the main path of the Indonesia Throughflow (ITF) and dynamics of thermal fronts. The aims of this study were to map the dynamic spatial and temporal of the thermal fronts, and to describe their implications to the pelagic fisheries. We used satellite data of sea surface temperature (SST) for the period of January-December 2018 with spatial and temporal resolutions of 4 km and monthly, respectively. For fishery data, we used sampling data of skipjack tuna fishing ground distributions in October and December 2018. Thermal fronts throughout the year were estimated using a Single Image Edge Detection (SIED) algorithm and the available fishing ground data were overlain on the SST front map. The results showed that the spatial distributions of thermal fronts along Makassar Strait tended to be different every month. However, the thermal fronts were consistently detected near the upwelling area from June to September. Skipjack tuna fishing grounds associated with fish aggregating devices (FADs) developed in the northern area of upwelling in October. Two month later, the FADs and free swimming skipjack fishing grounds again well formed around the same location. It implies that the formation of the thermal fronts after upwelling contributes the positive effect on development of pelagic fishery especially skipjack in Makassar Strait.